2022
DOI: 10.1002/pat.5650
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐modal cell structure formation of poly (lactic‐co‐glycolic acid)/superparamagnetic iron oxide nanoparticles composite scaffolds by supercritical CO2 varying‐temperature foaming

Abstract: Poly (lactic‐co‐glycolic acid) (PLGA)/superparamagnetic iron oxide nanoparticles (SPIONs) composite scaffold material was prepared by supercritical carbon dioxide varying‐temperature mode method. The multi‐modal cell structure was formed, and the mechanism was explained. The nuclei formed in the heating stage grew into large pores, while the nuclei formed in the depressurization stage grew into small pores. SPIONs caused pores to rupture and coalesce into small pores or large pores. The effects of foaming para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Wang et al [ 23 ] reported the fabrication of a multi-modal cell structure of PLGA using scCO 2 , Lee et al [ 24 ] produced microcellular foaming of PLGA polymer that exhibits micrometer-sized pores (~50 μm) and shows great potential for new surgical implants for controlled release of paclitaxel, and Alvarez et al [ 25 ] produced PLGA foams using CO 2 at high pressure but below supercritical conditions. Other authors have mixed the formation of PLGA foams with other polymers or compounds such as polycaprolactone (PCL) [ 26 , 27 ], poly(3,4-etilendioxitiofeno) (PEDOT) [ 28 ], bioglass particles/poly(lactide-co-glycolide) (BG/PLGA) [ 29 ], Sr/Zn n-HAp and PLGA [ 30 ], or (PLGA)/superparamagnetic iron oxide nanoparticles (SPIONs) [ 23 , 31 , 32 ]. Chitosan (Ch), a biodegradable polysaccharide extracted from crustaceans, has been shown to be safe and non-toxic in both animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 23 ] reported the fabrication of a multi-modal cell structure of PLGA using scCO 2 , Lee et al [ 24 ] produced microcellular foaming of PLGA polymer that exhibits micrometer-sized pores (~50 μm) and shows great potential for new surgical implants for controlled release of paclitaxel, and Alvarez et al [ 25 ] produced PLGA foams using CO 2 at high pressure but below supercritical conditions. Other authors have mixed the formation of PLGA foams with other polymers or compounds such as polycaprolactone (PCL) [ 26 , 27 ], poly(3,4-etilendioxitiofeno) (PEDOT) [ 28 ], bioglass particles/poly(lactide-co-glycolide) (BG/PLGA) [ 29 ], Sr/Zn n-HAp and PLGA [ 30 ], or (PLGA)/superparamagnetic iron oxide nanoparticles (SPIONs) [ 23 , 31 , 32 ]. Chitosan (Ch), a biodegradable polysaccharide extracted from crustaceans, has been shown to be safe and non-toxic in both animals and humans.…”
Section: Introductionmentioning
confidence: 99%